PENGARUH BUDAYA PERUSAHAAN DAN KOMITMEN PERUSAHAAN TERHADAP PERILAKU SOSIAL DALAM PERUSAHAAN PT. BRI (Persero) Semarang - Hilda Primahappy; Ari Pradhanawati; Sendhang Nurseto (Universitas Diponegoro, 2013)
This study aimed to determine the effect of cultural variables and the company's commitment to corporate social behavior within the company employees of PT. BRI (Persero) Branch Semarang. The population in this study were employees of BRI Semarang branch office. Samples were taken 60 respondents. Measurement scale using a Likert scale. In the analysis of the data using simple linear regression and multiple regression test with SPSS 15.00. Based on the survey results revealed a corporate culture category expressed a strong 71.7%, 70% category of the company's commitment powerful states, and categories of social behavior in the company (78.3%) stated either. F test results and corporate culture variables firm commitment variables are jointly significant effect on the social behavior of the variables in the company Fhitung> f table (4.0099> 24.031) so that Ha is accepted. The employees have a shared commitment to the work culture that generates social behavior and provide a positive impact to the company. Means to establish good cooperation between employees on corporate culture has a strong commitment to continue working in the company. Suggestions are given for PT. BRI (Persero) is to further improve the social behavior of the employees in the company should have a social life by providing the best service and It should further increase the commitment of employees to achieve work satisfaction.